S17. Trends in EEG monitoring and seizure occurrence in a cohort of neonates with congenital diaphragmatic hernia. (May 2018) - Massey, Shavonne L.; Danzer, Enrico; Hedrick, Holly; Rintoul, Natalie; Abend, Nicholas S.
Abstract : Introduction: Congenital diaphragmatic hernia (CDH) is a severe congenital anomaly that results in cardiopulmonary circuitry alterations and requires early life surgical intervention and utilization of extracorporeal membrane oxygenation. Both the underlying disease pathology and exposure to life-sustaining medical care increase the risk of brain injury. We describe the trends in electroencephalogram monitoring (EEG) and define seizure incidence and characteristics among a 17-year cohort of neonates with CDH receiving surgical repair. Methods: We conducted a single-center retrospective observational study of a cohort of neonates with CDH consecutively admitted for surgical repair at the Children's Hospital of Philadelphia between 1/1/1999 and 12/31/2016. EEG monitoring occurred after surgical repair when clinically indicated. Data collected included EEG duration; presence and type of nonepileptic events; and seizure descriptors. Results: Between 1999 and 2004, 47 neonates had CDH surgical repair and 2 EEGs were performed on 2 patients (4% EEG rate). Suspected seizure was the EEG indication for both patients and the median EEG duration was 60 h. Between 2005 and 2011, 55 neonates had CDH surgical repair and 41 EEGs were performed on 24 patients (44% EEG rate). The EEG indications were suspected seizure for 56% and encephalopathy for 44%. The median EEG duration was 29 h. Between 2012 and 2016, 47 neonates had CDH surgical repair and 70 EEGs were performed on 47 patients (100% EEG rate). The EEG indications were encephalopathy for 71% and suspected seizure for 29%. The median duration of EEG was 45 h. Nonepileptic events which had been concerning for seizures to bedside caregivers were prominent across the cohort (44% of EEG recordings), and the most common non-epileptic type was subtle autonomic event (76%). The incidence of seizures varied across the time periods. Between 1999 and 2004, seizure incidence across entire cohort was 2%, with 50% incidence of those who underwent EEG. Between 2005 and 2011, seizure incidence across the entire cohort was 15%, with 33% incidence of the cohort who underwent EEG. Between 2012 and 2016, seizure incidence was 13% as all patients underwent EEG. Subclinical seizures were present in 69%. The primary seizure onset sites were central (56%), occipital (25%), and temporal (25%). The most common electroclinical seizure semiology was clonic (38%). One patient experienced status epilepticus. Conclusion: Despite steady rates of surgical repair in a cohort of neonates with CDH, EEG monitoring dramatically increased over a 17 year span from 4% to 100%, with EEG being increasingly utilized to monitor encephalopathic neonates. Though seizure detection lessened with less targeted EEG monitoring, the incidence of seizure occurrence remained significant. Given the high incidence of subclinical seizures and frequent subtle events, EEG is an important neuromonitoring tool in this population to ensure adequate treatment of seizures without over-treatment of non-epileptic events.